2022 Playful Learning Conference Special Issue: Editorial - John Lean (Journal of Play in Adulthood, 2023)
This piece introduces this special issue of Journal of Play in Adulthood, outlining the six articles written by presenters at the 2022 Playful Learning Conference. It also highlights an emerging theme from these pieces; that of the playful objects that each article mentions. These objects are both created and used by educators and learners as part of their playful practice.